A Study of Short-term and Long-term Outcomes After Surgical Reconstruction of Syndactyly of The Hand - قاسم علي; ملحم فراس (Latakia University Journal -Medical Sciences Series, 2023)
Background: Syndactyly is a challenge to plastic surgeons because of its incidence and the effects it has on both the growth and the function of fingers. Most surgical techniques depend on skin grafts and dorsal skin flaps and both have multiple complications. Objective: Review short-term and long-term outcomes after surgical reconstruction of syndactyly of the hand Materials and Methods: 46 patients were included in this study who had 66 syndactylies that were surgically reconstructed. Patients’ ages ranged between 4 months and 13 years with a mean of 5.19 years and were divided into two groups depending on the use of skin grafting. The study reviewed the incidence of infection, skin necrosis, skin graft failure, web creep, scar assessment and contractures. Results: The study found a statistically significant difference between the occurrence of skin necrosis between techniques since it occurred only in the skin graft group. The study found a statistically significant difference between the occurrence of web creep and techniques since it occurred more in the skin graft technique. Using Vancouver scale for scar assessment, the study found a statistically significant difference between skin pigmentation and skin height and techniques while it found no statistically significant difference between scar pliability and vascularity and techniques. The study found a statistically significant difference between the occurrence of contractures and the use of skin grafting. Conclusions: Syndactyly reconstruction without skin grafting could lead to less short-term and long-term complications compared to using skin grafting.